The Reasonable Person for Our Time for Reasonableness in a Heterogeneous Society - Ceilia divakaran (Faculty of law Udayana University, 2017)
The cases of Bugmy and Munda decided by the High Court in 2013 raised the impact of social deprivation on Aboriginal defendants, in that it mars the development of an individual exposed to alcohol and alcohol-fuelled violence, and that full weight must be given to this in sentencing considerations. This significant legal precedent, in the backdrop of Aboriginal over-representation in the criminal justice system, invites the question of the relevance of the characterisation of the reasonable man in the law of provocation and delivery of equal justice, in a culturally heterogeneous society such as Australia. The case for constructing a contemporary reasonable man, clothed in Aboriginal identity, for equitable sentencing outcomes for Aboriginal defendants is explored.